BENTUK IMPLIKATUR PERCAKAPAN PADA UNGKAPAN PEMBERLAKUAN KURIKULUM 2013 DI SMK N 8 SURAKARTA - Prayogo, Hari; Sabardila, Atiqa (Universitas Muhammadiyah Surakarta, 2016)
This research aims to describe the form of implicatures found in conversationsÂ between students and teachers based on the implementation of the 2013 CuricullumÂ enactment in SMK N 8 Surakarta. This research is qualitative type which also uses thedescriptive method within it. The data sources of this research are the conversationsÂ between students and teachers. The samples of this research are expression of theÂ 2013 curicullum 2013âs enactments in SMK N 8 Surakarta. The data collectingÂ technique in this research is attentive method followed by quotation method. TheÂ analysis technique is the selection elements determined by the selection of pragmatic.Also, this research uses an advancing step that is connect-compare with the standardÂ variety. The results can be clarified in eight types. They are (1) implicature with theÂ intention to explain, (2) implicature with the intention of complaining, (3) implicaturewith intention of asking, (4) implicature with intention to satirize, (5) implicature withÂ the intention of the prediction, (6) implicature with the intention of the skepticismÂ (7) implicature with the intention of the are a speeches and (8) implicature with theÂ intention of the appealing.